Assessing the performance of WaSim and DRAINMOD models for subsurface drainage design and analysis in a data-scarce environment - Malota, M.; Taguta, C.; Dirwai, Tinashe Lindel; Mabhaudhi, Tafadzwanashe; Senzanje, A. (American Society of Agricultural and Biological Engineers, 2024)
Simulation models are useful decision-support tools for designing and analyzing subsurface drainage systems in irrigated lands. However, the challenge is determining the soil hydraulic data inputs required by models to achieve reliable and accurate simulation of water table depths (WTDs) and drainage discharges (DDs) at various drain depths and spacing combinations. This is particularly important for data-scarce areas, such as middle- and low-income countries (MLICs), that lack facilities to determine in-situ soil hydraulic properties. We evaluated the performance of WaSim and DRAINMOD models to simulate WTDs and DDs at a field scale in KwaZulu-Natal, South Africa. Saturated hydraulic conductivity (Ksat) and soil water retention ( (h)) values were determined using the in-situ pumping test and a pressure plate apparatus. Pedotransfer functions (PTFs) in the Rosetta computer program also estimated these soil parameters. The DRAINMOD and WaSim models were calibrated using the in-situ measured Ksat and laboratory-measured (h) data, while the validation exercise used the PTFs-estimated Ksat and (h) data as soil hydraulic inputs. The models’ performance in simulating WTDs and DDs was assessed using Nash-Sutcliffe Model Efficiency (NSE), Modified Index of Agreement (d), Coefficient of Determination (R2 ), and Mean Absolute Error (MAE). During validation, DRAINMOD simulated WTDs with NSE, d, R2 , and MAE of 0.86, 0.81, 0.89, and 5.3 cm, respectively, whereas, for DDs, the model registered NSE, d, R2 , and MPE of 0.81, 0.79, 0.83, and 0.17 mm.day-1, respectively. During the validation period, the WaSim model simulated WTDs with NSE, d, R2 , and MAE of 0.76, 0.74, 0.78, and 9.0 cm, respectively. For the same validation period, the WaSim model simulated DDs with NSE, d, R2 , and MAE of 0.74, 0.73, 0.77, and 0.2 mm.day-1, respectively. The results suggest that both models, with either in-situ measured and laboratory-measured soil data or PTFs-estimated soil data, can be used to design and analyze drainage systems in data-scarce environments with a reasonably high confidence level. Designers of subsurface drainage systems in Pongola, South Africa, can use any of the two drainage models as decision support tools. We recommend using DRAINMOD and WaSim models with PTFs-estimated hydraulic soil data based on soil textural information, soil particle size data, bulk density, and (h) data at field capacity and permanent wilting point.